Transactivation by the p65 subunit of NF-kappaB in response to interleukin-1 (IL-1) involves MyD88, IL-1 receptor-associated kinase 1, TRAF-6, and Rac1 - BOWIE, ANDREW; O'NEILL, LUKE ANTHONY JOHN (American Society for Microbiology (ASM), 2001)
We have examined the involvement of components of the interleukin-1 (IL-1) signaling pathway in the transactivation of gene expression by the p65 subunit of NF-kappaB. Transient transfection of cells with plasmids encoding wild-type MyD88, IL-1 receptor-associated kinase 1 (IRAK-1), and TRAF-6 drove p65-mediated transactivation. In addition, dominant negative forms of MyD88, IRAK-1, and TRAF-6 inhibited the IL-1-induced response. In cells lacking MyD88 or IRAK-1, no effect of IL-1 was observed. Together, these results indicate that MyD88, IRAK-1, and TRAF-6 are important downstream regulators of IL-1-mediated p65 transactivation. We have previously shown that the low-molecular-weight G protein Rac1 is involved in this response. Constitutively active RacV12-mediated transactivation was not inhibited by dominant negative MyD88, while dominant negative RacN17 inhibited the MyD88-driven response, placing Rac1 downstream of MyD88 on this pathway. Dominant negative RacN17 inhibited wild-type IRAK-1- and TRAF-6-induced transactivation, and in turn, dominant negative IRAK-1 and TRAF-6 inhibited the RacV12-driven response, suggesting a mutual codependence of Rac1, IRAK-1, and TRAF-6 in regulating this pathway. Finally, Rac1 was found to associate with the receptor complex via interactions with both MyD88 and the IL-1 receptor accessory protein. A pathway emanating from MyD88 and involving IRAK-1, TRAF-6, and Rac1 is therefore involved in transactivation of gene expression by the p65 subunit of NF-kappaB in response to IL-1.
PUBLISHED
Keywords: Biochemistry